Expansive Soil Treatment with Liquid Ionic Soil Stabilizer. Issue 52 (December 2018) - He, Shi; Yu, Xinbao; Banerjee, Aritra; Puppala, Anand J.
Calcium-based stabilizers such as lime and cement control swell and shrinkage behavior and enhance strength properties for expansive soils through the formation of pozzolanic components. However, sulfate-bearing subgrade soils stabilized with calcium-based stabilizers might cause excessive swelling and shrinkage due to the formation of highly expansive minerals like ettringite and thaumasite. In this paper, one liquid ionic soil stabilizer (LISS) was evaluated as an alternative stabilizer used to control swelling and shrinkage behavior of expansive soils. A comprehensive laboratory experiment program including a linear shrinkage test, a one-dimensional swell test, and an unconfined compressive strength test, was designed and carried out on soils from Dallas, Texas before and after treatment. Three dosage levels of stabilizer and four different curing periods were investigated. Test results indicate that LISS is an effective stabilizing agent, which not only reduces swelling and soil plasticity but also increases soil strength. Furthermore, a similar type of LISS is utilized to treat the soil in Dallas via deep injection using a hydraulic pump. Field emission scanning electron microscopy results on the test soil showed that the stabilizing program is likely to work through clay flocculation and morphological variations in the clay particles.